Pendidik di atas garis dalam menyongsong masyarakat ekonomi asean - Ni Wayan Ayu Santi (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
Educators at the top of the line offering basic concepts toward mental revolution that build awareness creating role models. The glory of the profession as an educator is the second leading fort after the parents that need to have enlightened attitudes. The purpose of this paper is (1) to provide knowledge of educators on the line, (2) gives a conceptual representation to be educators in the top line, and (3) providing knowledge attitude of educators on the line to welcome the Asean Economic Community (AEC). Educators at the top of the line will be effective in facing the MEA as a barometer of success educators views of learners produces. The essence of the concept of educators on the line should earlier have and practice ourselves to be educators in the top line resulting learners over the line include skills (1) responsible, (2) freedom, (3) a solution, (4) the willingness and (5) selection, or abbreviated to "Terkesimalah". Related to the above, education moto of Ki Hajar Dewantara actually be understood by educators at the top of the line so as to have an attitude in facing the MEA, among others, (1) Ing Ngarso Sung Tulodo, (2) Ing Madya Mangun Karso (3) Tut Wuri Handayani.Keywords: Educator, On Top Line, MEA http://dx.doi.org/10.17977/um022v1i12016p027